Tradução de humor: a barreira cultural/linguística da tradução de piadas na legendagem do seriado Modern Family - Ribeiro Neto, João Antonio Pimenta (2019)
This study is part of the field of Audiovisual Translation, which establishes a common interface between subtitling and translation of humor. Subtitling is characterized as the translation practice that consists of the presentation of a written text, usually at the bottom of the screen, and which proposes to show the dialogues of the talking characters, the discursive elements of the image as the texts shown in signs or billboards, and elements of the soundtrack as the voices in off. Marta Rosas observes in her book Humor Translation (2002) two main problems in this kind of translation. The first one is the non-existence of cultural references between the members of the two languages and cultures involved and the second one is the non-correspondence between the languages/cultures on any linguistic level. This research proposes to comparatively analyze humor translation, based on the definition of Bagno's stigmatized variety (1997), in two different types of subtitles from a TV show called Modern Family in five scenes of its first season. The author uses the term “stigmatized” to refer to all the linguistic aspects that constitute the speech of individuals that dwell in poor areas with no access to the use of standard language. The subtitles to be analyzed are the commercial ones, found in the official DVD of the show and the subtitles of fans, (fansubs), available on the internet. This research also proposes to verify if the two types of subtitles followed two technical aspects established in the parameters of Diaz-Cintas and Remael (2007), which are the amount of time that the subtitle remains on screen and the amount of characters used in the subtitles, and whether that same amount of characters respects the limit set by the amount of time the caption is displayed on the screen.